Critical comparison of polydisperse kinetic theories using bidisperse DEM data. (14th December 2022) - Shi, Kun; He, Mingming; Zhang, Li; Zhao, Bidan; Wang, Junwu
Highlights: Kinetic theories for polydisperse flow were reviewed. Polydisperse kinetic theories were assessed using DEM data. Polydisperse kinetic theories for one-dimensional shear flow were studied. Abstract: Kinetic theories have been developed to describe the hydrodynamics of polydisperse granular flows under different theoretical assumptions. In this study, six species theories are assessed using the DEM data obtained from simple shear flow containing bidisperse particles with low and moderate solid volume fraction (Galvin, 2007). It was shown that (i) only the theories of Iddir and Arastoopour (2005) and Zhao and Wang (2021) can qualitatively capture all of the effects of various parameters on the granular temperature ratio and the normal and shear stresses; (ii) the granular temperature ratio can be predicted accurately either by Iddir and Arastoopour (2005) or Zhao and Wang (2021), depending on the input parameters; and (iii) the predictions of normal and shear stresses by Iddir and Arastoopour (2005) are superior in matching the DEM data for most tested cases. Present study not only discusses the fundamental differences between different species kinetic theories, but also offers a critical assessment of their suitability in modeling simple shear flow.